Sweetness at the Bottom of the Pie - Bradley, C. Alan (New York : Bantam Books Trade Paperbacks, 2010)
It is the summer of 1950 - and at the once-grand mansion of Buckshaw, young Flavia de Luce, an aspiring chemist with a passion for poison, is intrigued by a series of inexplicable events: A dead bird id found on the doorstep, a postage stam bizarrely pinned to its beak. Then, hours later, Flavia find a man lying in the cucumber patch and watches him as he takes his dying breath. For Flavia, who is both appalled and delighted, life begins in earnest when murder comes to Buckshaw. "I wish I could say I was afraid, but I wasn't. Quite the contrary. This was by far the most interesting thing that had ever happened to me in my entire life."
Keywords: Detectives -- England; Motherless families; Sisters; England; Mystery fiction